Benthic response to upwelling events off the SE Brazilian coast - Sumida, PYG; Yoshinaga, M. Y.; Ciotti, A. M.; Gaeta, S. A. (Inter-research, 2005)
The main aim of the present study was to evaluate and compare temporal responses of the benthos in 2 continental shelf areas (Cabo Frio and Ubatuba) off the SE Brazilian coast. In Cabo Frio (23 degrees S, 42 degrees W), the western boundary coastal upwelling of the South Atlantic Central Water (SACW) enhances primary productivity, potentially increasing food supply to the benthic communities via sinking of particulate organic carbon (POC). In contrast, POC fluxes in Ubatuba (23 degrees S, 45 degrees W) are expected to be comparatively lower because SACW remains subsurface. We analyzed the temporal and spatial input of phytodetritus (concentration of chlorophyll a in sediments) and the benthic microbial biomass (estimated by ATP-based carbon content in sediments). Median surface chlorophyll concentration was computed for all daily available SeaWiFS images (from 2001 and 2002) to follow chlorophyll a inputs. All parameters used to investigate benthic responses in the study areas showed consistently higher values in Cabo Frio than in Ubatuba. The results showed that benthic response to upwelling may last months, fueling the microbial communities in the Cabo Frio region.
Keywords: benthic-pelagic coupling; benthic microbial response; SE Brazilian continental shelf